Linguistically Grounded Techniques for English in the Professional Institutions of Rural India - Kumari Pragyan (Bandar Lampung University (UBL), 2013)
This paper discusses some of the linguistically grounded techniques for teaching English. It sets up the story of English in the context of education in India. Its implications in the professional institutes would help students become aware of the intricacies of language. This awareness will help overcome difficulties in learning English. Students in professional institutes can be prepared with this methodology to acquire English not only as a second language but as a part of international education. It would provide them a landscape through which it is possible to take various journeys; its horizons are redefined by each approach.